THE EFFECT OF THE PROBLEM-BASED LEARNING MODEL ON THE SCIENTIFIC ARGUMENTATION ABILITY OF STUDENTS ON ENVIRONMENTAL POLLUTION MATERIALS - Riska Wahyuni; Halim Simatupang; Santi H (UNIVERSITAS NEGERI MEDAN, 2022)
The purpose of this study was to determine the effect of implementing the Problem Based Learning (PBL) learning model on the ability of scientific argumentation and how much influence the PBL learning model has on the scientific argumentation ability of students on environmental pollution material in class VII, 1st Junior High School Angkola Muaratais. This study uses a true experiment method with a pretest-posttest control group design. The population in this study were all students of class VII, with two samples, namely the experimental and control classes. There are two samples in this study, namely the experimental class and the control class. The sampling technique used is simple random sampling. Randomly selected samples were from classes VII-A and VII-B. The research instrument used is a scientific argumentation ability test instrument using five essay questions. Analysis of the data used in this study was performed by performing an independent sample t-test and a Cohen's d test. The results of the pretest showed that the initial abilities of students in grades VII-A and VII-B were the same. Class VII-A was chosen as the experimental class, and Class VII-B was chosen as the control class. After that, treatment was given using the PBL learning model in the experimental class and conventional learning using the lecture and question and answer method in the control class. Based on the posttest results, it was found that the PBL learning model had a significant effect on the ability of scientific argumentation on environmental pollution material in class VII 1st Junior High School Angkola Muaratais with a value of tcount > ttable (3.828 > 1.684) using the independent sample t-test test. The influence of the PBL learning model on students' scientific argumentation skills is categorized as strong, with a Cohen's d value of 1.168. It can be concluded that the PBL learning model can have a significant influence on students' scientific argumentation skills and the effect obtained is strong.